THE DIFFERENCE IN SALIVARY pH ON REMOVABLE ORTHODONTIC APPLIANCE BEFORE AND AFTER IMMERSION WITH SORBITOL - Henry Anthonio Gozali; Pricillia Priska Sianita (Journal of Health and Dental Sciences, 2022)
ABSTRACT Orthodontic treatment with removable orthodontic appliances requires the patient's commitment to use the appliance in the mouth at a certain time. It can lead to specific changes in the mouth, such as a decrease in the level of acidity or pH of the mouth, which may be associated with increased biofilm accumulation. The acidity level of saliva in the mouth is an important factor in several oral problems, such as dental caries and periodontal disease. The use of mouthwash is still one of the simple ways that are widely used to overcome these problems. Among the many types of mouthwash on the market, sorbitol mouthwash is an option that can be used to prevent changes in the acidity level of saliva from reaching a critical value of < 5.5 and endangering the oral health of orthodontic patients. This study aims to determine the change in salivary pH of patients in orthodontic treatment with removable appliances before and after immersion with sorbitol mouthwash. The research method was an experimental laboratory study conducted with pre-test and post-test designs involving 33 samples divided into three groups, each consisting of 11 samples. Immersion time is divided into three categories, namely 15, 30, and 60 seconds. A pH indicator measures the level of saliva acidity. The results show that there are different changes in pH in each period of immersion. The conclusion was that immersion in sorbitol mouthwash resulted in changes in the pH level of saliva in removable orthodontic appliances, and the sufficient soaking time is 15 seconds. DOI : 10.54052/jhds.v2n2.p317-328